Development of spouse-inclusive framework for digital management of perinatal depression and anxiety - kamaruddin, amalia; Mohd Arifin, Siti Roshaidai; Nurumal, Mohd. Said; Mohd Mohadis, Hazwani; Muhammad, Noor Azimah; Nik Hussain, Nik Hazlina; Wardaningsih, Shanti (Universiti Kebangsaan Malaysia, 2023)
Introduction: Spouse-inclusive intervention has been found effective to improve perinatal mental health, yet it was commonly delivered face-to-face, requires high commitment from spouses as well as healthcare professionals, therefore is not sustainable. While several digital applications demonstrate modest success in reducing the symptoms of depression and anxiety, the spouse’s participation in such an approach is limited. Therefore, this study aimed to explore perspectives, preference, and information or educational needs of perinatal women and their spouse regarding spouse-inclusive intervention. Materials and Methods: Using a generic qualitative research design, in-depth interviews were conducted with 20 perinatal women (with symptoms of depression and anxiety) and 15 men (spouses) in the obstetrics and gynecology clinics in Sultan Ahmad Shah Medical Centre and Hospital Canselor Tuanku Muhriz. Interview data were analysed using framework analysis. The selected participants in this study were chosen using one of these methods: Edinburgh Postnatal Depression Scale (EPDS) score ≥12 or Depression Anxiety Stress Scale (DASS) score ≥8 for depression, ≥7 for anxiety. Results: Three main themes were identified from the interview which include: (i) adjusting to a new period of life, (ii) dealing with perinatal distress, and (iii) mobilising needs and support. While spouse support was perceived by the perinatal women one of the contributing factors to depression and anxiety, financial constraint was seen by the men (spouses) as the major factor leading to depression and anxiety. Both women and spouses preferred to have a user-friendly online intervention to obtain knowledge on maternal mental health. They expressed their informational needs on communication skills, depression and anxiety cues, self-screening, childcare management, perinatal care, and coping mechanism. Conclusion: Perinatal women (with depression and anxiety) and the spouses acknowledge that mental health apps that include spouses’ participation will help in reducing the symptoms that can contribute to depression and anxiety.